If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 4 = 12x + -16 Reorder the terms: 4 + 10x = 12x + -16 Reorder the terms: 4 + 10x = -16 + 12x Solving 4 + 10x = -16 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 4 + 10x + -12x = -16 + 12x + -12x Combine like terms: 10x + -12x = -2x 4 + -2x = -16 + 12x + -12x Combine like terms: 12x + -12x = 0 4 + -2x = -16 + 0 4 + -2x = -16 Add '-4' to each side of the equation. 4 + -4 + -2x = -16 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -16 + -4 -2x = -16 + -4 Combine like terms: -16 + -4 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 3+2(x-1)=4x | | 3+2n-6=25 | | 8z+11=7z+5 | | 4(12n-6)=6(-4+5n)+18n | | 2x-2.8-2.4x+2.6x-5= | | 6(-3-x)-2*x=14 | | 6sec^2(0)-2sec^2(0)= | | 4x^4+21x^2-18=0 | | -7=7-(8-a) | | Y=50+1x | | yz^2-z^2+5+3yz-3z^2+4yz= | | 16=7-(b+9) | | (x-1)(x+3)=(x+2)(x-3) | | -2*x+8=-16 | | -3x+4y=46 | | 5y-7y-6=2 | | 14=7p-ap | | 6x-6=-216 | | -6*x=42 | | 6x-4+5x=-26 | | 7y-2=6y^2 | | 5m^2-85m=0 | | x^2-17x+70=10 | | 4c^2+12x-44=0 | | 16x^2-9y^2+36y+108=0 | | Y=(-3)(4i)(7i) | | 7x-(4x+3)=1 | | [3y-2]=[26-4y] | | 16y-6=2 | | -x+9-9= | | 121x^2-16=-7 | | T*23=276 |